Assessing the Use of an Oral Health Literacy Toolkit in Three California Dental Practices: A Mixed-Methods Feasibility Study - Yeeda, Evangelin; Tseng, Winston; Neuhauser, Linda; Ivey, Susan; Liu, Jessica; Latham, Lesley; Ta, Michelle; Robinson, Lindsey (Journal of the California Dental Association, 2025)
Background This study evaluates the California Oral Health Literacy Toolkit for enhancing patient and oral health care provider communication in California dental offices. Only 1 in 10 adults in the U.S. fully understands written health materials. This study examines communication between providers and patients and documents the challenges and successes of implementing the toolkit.Methods This study was conducted at three California dental practices. Methods included nine key informant interviews, an online survey to assess oral health literacy (OHL) capacity and readiness, field observations, and a review of practice informational materials to examine communication and the implementation of the toolkit.Results The three main successes of toolkit implementation were its adoption by the dental clinics, the identification of OHL leaders/teams, and the use of the teach-back method as a communication strategy. Challenges included the time required to implement the toolkit, staff turnover, and difficulty aligning educational materials with patients’ literacy levels.Conclusions The toolkit aims to improve communication between oral health care providers and patients, creating a better practice environment. This study found that the toolkit helped providers create a more patient-centered environment and use clear communication techniques, including teach-back. This suggests that the toolkit can help advance oral health literacy and health equity. It also identified ways to minimize barriers and improve the toolkit.Practical Implications The study provides insights into effective strategies and barriers for implementing the toolkit, which can inform future efforts to improve oral health literacy in dental practices.